2005
DOI: 10.1099/jmm.0.45832-0
|View full text |Cite
|
Sign up to set email alerts
|

Spore shedding pattern of Enterocytozoon bieneusi in asymptomatic children

Abstract: Stool samples from seven human immunodeficiency virus (HIV)-negative and two HIV-positive children with asymptomatic Enterocytozoon bieneusi infections were daily examined to quantify spore shedding using Gram-chromotrope staining under light microscopy. The spore shedding pattern and intensity in these children was variable. Mean spore concentrations in the stool samples from these children ranged from 2.4 × 102 to 1.2 × 105 spores per gram. Light microscopy could detect spores in stool specimens for 9–33 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 22 publications
2
13
0
1
Order By: Relevance
“…The patterns of the incidence were similar to those observed for the prevalence. This finding suggests that E. bieneusi infection is a self-limited, short-course disease, which is also supported by our previous study showing that the number of excreted spores tended to decrease and disappear after a period of time (14). A few studies demonstrated that E. bieneusi infection was significantly prevalent in children between 1 and 3 years of age (10,21).…”
supporting
confidence: 69%
“…The patterns of the incidence were similar to those observed for the prevalence. This finding suggests that E. bieneusi infection is a self-limited, short-course disease, which is also supported by our previous study showing that the number of excreted spores tended to decrease and disappear after a period of time (14). A few studies demonstrated that E. bieneusi infection was significantly prevalent in children between 1 and 3 years of age (10,21).…”
supporting
confidence: 69%
“…The concentrations of spores (of unspecified spe-cies) in HIV/AIDS adults varied from 4.5 ϫ 10 5 to 4.4 ϫ 10 8 /ml (17). Thus, the concentration of E. bieneusi spores observed in the present study (range, 3.5 ϫ 10 3 to 4.4 ϫ 10 5 /ml; mean, 8.8 ϫ 10 4 /ml) falls within the reported ranges (17,28). However, even in specimens with high spore counts, clumping of spores as reported previously (17) was not observed in the present study, which most likely is related to the long-term storage in formalin.…”
Section: Resultssupporting
confidence: 62%
“…Studies on the intensity of intestinal microsporidiosis showed that there are significant temporal variations in the concentration of E. bieneusi spores shed by HIV/AIDS patients (4,17,28). The mean spore concentration varied in HIVpositive children from 2.4 ϫ 10 2 to 1.2 ϫ 10 5 /g, and the maximum concentration reached 5.7 ϫ 10 5 /g in a HIV-negative child (28). The concentrations of spores (of unspecified spe-cies) in HIV/AIDS adults varied from 4.5 ϫ 10 5 to 4.4 ϫ 10 8 /ml (17).…”
Section: Resultsmentioning
confidence: 99%
“…Spore shedding of E. bieneusi in asymptomatic humans and pigs was intermittent and sometimes too low to be detected under a microscope (1,15). Therefore, assessing fecal samples by microscopic examination might underestimate the prevalence of E. bieneusi infection.…”
mentioning
confidence: 99%